Pengaruh Persistensi Laba, Risiko Sistematik, dan Faktor lainnya terhadap Earnings Response Coefficient - Putri Aulia Afifah; Arya Pradipta; Dicky Supriatna (Media Bisnis, 2023)
This study aims to obtain empirical evidence of factors that influence the earnings response coefficient. The independent variables in this study are capital structure, systematic risk, company size, growth opportunity, profitability, and earnings persistence. While the dependent variable in this study is the earnings response coefficient (ERC). The object in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. A total of 50 companies with a total of 147 data were obtained using the purposive sampling method and was tested with the moderating regression analysis method. According to the hypothesis test, the result of this study is that capital structure, systematic risk, firm size, growth opportunities, profitability, and earnings persistence have no effect on the earnings response coefficient. No effect means that the increase or decrease capital structure, systematic risk, company size, growth opportunities, profitability and earnings persistence will not affect the market reaction to earnings announcements, thus that not reflect the value of earnings response coefficient.